2018
DOI: 10.1016/j.aott.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison of the proximal crescentic osteotomy and rotational scarf osteotomy in the treatment of hallux valgus

Abstract: ObjectivesThe aim of this study was to compare clinical and radiological results of proximal crescentic osteotomy (PCO) and rotational scarf osteotomy performed in the treatment of hallux valgus.MethodsA total of 57 consecutive patients (60 feet) with symptomatic hallux valgus deformity were randomly assigned to one of two groups. The PCO group consisted of 22 women and 5 men (30 feet) and the mean age was 43(±14.5) years. The scarf group consisted of 23 women and 7 men (30 feet) and the mean age was 40.9(±12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
(41 reference statements)
1
14
0
Order By: Relevance
“…Bene ts of the proximal crescentic osteotomy combined with a distal soft-tissue procedure have been described for the correction of severe hallux valgus in many literatures [12,20]. This technique was popular for correction of hallux valgus associated with metatarsus primus varus in a report [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bene ts of the proximal crescentic osteotomy combined with a distal soft-tissue procedure have been described for the correction of severe hallux valgus in many literatures [12,20]. This technique was popular for correction of hallux valgus associated with metatarsus primus varus in a report [20].…”
Section: Discussionmentioning
confidence: 99%
“…The open-wedge osteotomy resulted in a slight lengthening of the rst metatarsal (1-2 mm) [27].But only very few prospective randomized researches have been reported to compare two different kinds of techniques of correction for hallux valgus. Sahin et al [12] made a report about the comparison of rotational scarf osteotomy and proximal crescentic osteotomy in correction of the hallux valgus. The proximal crescentic osteotomy and scarf osteotomy combined with the distal soft tissue procedures provided similar satisfactory correction, clinical and radiological results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our osteotomy method improved the three main radiographic parameters of HV: HVA, IMA, and DMAA. The IMA and HVA are objective parameters for assessing corrections performed in each type of osteotomy [24, 25], while the DMAA is commonly used to quantify articular deformity [34, 35]. The DMAA is one of the most important radiographic angles in HV, and it has been shown that non-correction of DMAA alterations is associated with early recurrence of the deformity, reduced range of motion of the metatarsophalangeal joint, and pain [3638], and so correcting the increased DMAA is key to a satisfactory surgical outcome.…”
Section: Discussionmentioning
confidence: 99%